Pengelolaan Sumber Daya Tumbuhan, Studi Kasus di Desa Jambusari - Rifqi Ilham; Tri Cahyanto (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This study aims to explore the local wisdom of the Jambusari Village community, Cilacap, in managing plant resources, especially the practice of chewing betel nut and smoking traditional plants. The research method used is a qualitative approach with a case study design, involving 44 respondents selected through snowball sampling techniques. The results of the study indicate that the habit of chewing betel nut and smoking is an integral part of the local culture that is passed down from generation to generation. As many as 75% of respondents came from families who had the habit, with the majority stating that they had not experienced any changes in this practice. Although there are benefits perceived from both habits, such as freshness and enjoyment, there are also reports of negative impacts on health. This study highlights the importance of preserving ethnobotanical knowledge as an effort to conserve local biological and cultural resources.